Cooperation for the Prevention of Homelesness Using Examples of Selected Countries of the European Union - Szluz, Beata (Jan Evangelista Purkyne in Usti nad Labem, 2015)
Partnerships between the various institutions are important for a given entity in the process of engaging stakeholders. They lead to the solution of problems that affect all partners. In the context of partnership, individuals, groups and organisations representing different sectors agree to cooperate. Their aim is the fulfillment of their obligations or to undertake specific tasks, bringing their skills and resources together, incurring the risks and costs, and sharing the benefits resulting from the achievement of common partnership goals and the objectives of individual member organisations. Cross-sectoral partnership consists of representatives of the three sectors. These are usually large partnerships entered into with the aim of implementing national, regional, and even international projects, among others, in terms of social assistance. This article illustrates selected examples of actions taken on behalf of homeless individuals that are implemented by entities representing the various sectors, undertaking to cooperate and implement projects for the benefit of this social category.
Keywords: homelessness; social policy; the European Union; partnership